Picobia dziabaszewskii sp. nov. (Acari, Syringophilidae)—combined description (morphology with DNA barcode data) of a new quill mite species parasitizing Garrulax formosus (Passeriformes: Leiothrichidae) - Glowska, Eliza; Dragun-Damian, Anna; Dabert, Jacek (Zootaxa, 2012)
A new species of quill mites Picobia dziabaszewskii sp. nov. (Acari, Syringophilidae) parasitizing Garrulax formosus(Verreaux) (Passeriformes: Leiothrichidae) is described using combined data sources: standard morphological informa-tion extended by mitochondrial cytochrome oxidase I sequence (COI) and domene D2 of the nuclear gene 28S rDNA data(DNA barcode). Additionally, the case of polymorphism within domene D2 region of 28 rDNA is registered for the first time in syringophilid mites.